Insights into bunyavirus architecture from electron cryotomography of Uukuniemi virus. - Overby, A; Pettersson, R; Grünewald, K; Huiskonen, J (2008)
Bunyaviridae is a large family of viruses that have gained attention as "emerging viruses" because many members cause serious disease in humans, with an increasing number of outbreaks. These negative-strand RNA viruses possess a membrane envelope covered by glycoproteins. The virions are pleiomorphic and thus have not been amenable to structural characterization using common techniques that involve averaging of electron microscopic images. Here, we determined the three-dimensional structure of a member of the Bunyaviridae family by using electron cryotomography. The genome, incorporated as a complex with the nucleoprotein inside the virions, was seen as a thread-like structure partially interacting with the viral membrane. Although no ordered nucleocapsid was observed, lateral interactions between the two membrane glycoproteins determine the structure of the viral particles. In the most regular particles, the glycoprotein protrusions, or "spikes," were seen to be arranged on an icosahedral lattice, with T = 12 triangulation. This arrangement has not yet been proven for a virus. Two distinctly different spike conformations were observed, which were shown to depend on pH. This finding is reminiscent of the fusion proteins of alpha-, flavi-, and influenza viruses, in which conformational changes occur in the low pH of the endosome to facilitate fusion of the viral and host membrane during viral entry.